A Study on Different Laboratory Methods for Diagnosis of Intestinal Protozoal Infections - Shahid, SB; Wazib, A; Chowdhury, A; Shamsuzzaman, SM; Mamun, KZ (Bangladesh Medical Journal, 2014)
This cross sectional study was done from January 2009 to June 2010 in Microbiology department of Dhaka Medical College, Dhaka on different laboratory methods for diagnosis of intestinal protozoal infections and their distribution among selected study population. Of the 375 stool samples evaluated, 103 (27.5%) samples were positive for the intestinal protozoa. The prevalence of G. intestinalis was highest (25.78%) followed by E. histolytica/dispar (8.98%). Other protozoa found were, E. coli (1.56%), B. hominis (1.95%), C. mesnilli (1.17%) and C. parvum (0. 78%). lron-hematoxyline stain showed highest sensitivity for detection of protozoa. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18510 Bangladesh Medical Journal 2011 Vol.40(2): 47-49